Factors that affect the job preferences of graduating college students enrolled in business courses in Iloilo City - Calamohoy, Kathleen Kaye A.; Dalida, Lenard L.; David, Klaire Dominique N.; Escobar, John Emil P.; Tabangay, Angelica Jazz Marie R. (2017.)
Job pertains t the particular duty or function of a person within an organization which creates his/her identity or role. Given a wide variety of industry nowadays, students have specific job preferences in mind when looking for a job. Because of this, the study aims to determine the significant factors that affects the job preference of graduating students enrolled in business courses in Iloilo City. With the use of convenience sampling, the researchers gathered data from 99 respondents, 74 of which are females and 25 are males with diverse socio-demographic characteristics. This paper attempts to determine the job preferences of the graduating business students as well as examine the factors that affect such preference. The Weighted Mean and standard dDeviation was used to analyze the intrinsic and extrinsic factors affecting the students' job preferences. Upon examination of the results, it has been discovered that some of the socio-demographic factors such as gender, social background, and location of home address do not have significant effect on the job preference of graduating business students. analysis of the results also showed that from the 11 factors identified into affect the job preferences of students, Interest in the work was deemed to be the first in terms of extreme importance. This study could be used a reference by the human resource Manager of different companies in Iloilo City in targeting qualified applicants as well as to assist in making future recruitment strategies and improve the current selection and hiring processes. Future researchers can also use this study as a reference about the job preference of students in Iloilo City and are encouraged to use statistical methods other than convenience sampling to get the accurate representation of the population.
Research Paper (Mgt 199-Management Research). -- [Iloilo City] : University of the Philippines Visayas-College of Management, December 2017.